ISLAM DALAM PERGUMULAN KEBUDAYAAN KONTEMPORER - Fadhliah Mubakkirah (Fakultas Syariah Institut Agama Islam Negeri Palu, 2016)
Religion (Islam) derived from revelation and has its own norms. Since it is normative, it then is likely to become permanent. On the other hand, culture is man-made and therefore it develops in accordance with time and tend to constantly change. Meanwhile, Islamic culture bases on Islamic values itself videlicet Qur'an and Hadith. As long as those customs and cultures are not against Islam, people are pleased to do so. However, if it is contrary to Islamic school, those cultures are inevitably unallowed.